A Product Attribute Influencing Halal Product Purchase Decisions: A Field Study In Bogor - Andika Nuraga Budiman; Hilma Suyana (Majalah Sainstekes, 2022)
Every consumer, especially Muslim consumers, demands that a product be halal. Whether it's food, medicine, or consumer products. However, the application of Islamic teachings in laws and regulations governing the provision of halal guarantees on food creates a challenge in the regulation governing the provision of halal labels on food. Due to the lack of tenacity in existing rules and regulations governing the use of halal labeling on food, haram food products continue to circulate in Indonesia. Halal products are the most important to Muslim consumers. We investigated Muslims’ attitudes toward halal products in the Bogor area. This study involved 155 respondents who consume halal products. Data for this study was gathered by by using an interview as the primary data collection method, through a personality-administered questionnaire. The respondents are Muslim consumers who only purchase and consume halal products. The regression approach was used in this study, which aimed to connect cause-effect linkages through each variable, primarily to investigate the impact of product qualities on purchase decisions. The results reveal that the quality of Halal products obtained is encouraging for responders in Bogor. This leads to our research finding that the halal product is of such high quality that consumers desire to buy it. Meanwhile, according to the findings on perceived price, consumers do not consider or object to the prices supplied by halal items, despite that generally pricing is one of attributes for consumer’s purchasing decision